Viviparous reproduction in the land snail Idyla (Pulmonata: Clausiliidae) from Greece: a disadvantageous inheritance?. (14th March 2019) - Sulikowska-Drozd, Anna; Apostolopoulou, Konstantina; Giokas, Sinos; Schilthuizen, Menno
Abstract: Viviparity in land snails occurs mainly in species living in tropical or harsh mountain habitats, both of which are characterized by high humidity. The clausiliid Idyla bicristata (Rossmässler, 1839) is an exception. This viviparous snail inhabits the Mediterranean region, which is characterized by long, dry summers. Here, based on field and laboratory breeding observations and experiments, we describe the phenology and fecundity of I. bicristata in detail. The species follows a seasonal pattern of activity: snails are active from October until April (but not in January), and aestivate during the summer months. Reproduction occurs in autumn and spring, with a peak in October, when about 50% of adults were found to be gravid, with an average of 4.9 embryos/adult. In laboratory cultures, adults usually produced neonates twice a year, and the annual fecundity of a pair averaged 15.7 neonates. Reproductive maturity was attained 6.5–7 months after birth. We also investigated the effect of a two-month long experimental drought on gravid snails. We found that the reproductive period was long and flexible, with a low number of individuals being gravid at a given time (in comparison to other viviparous snails). This strategy may reduce the risk of failure and may be a response to demanding climatic conditions. The widespread occurrence of viviparous reproduction in related taxa, which inhabit mainly mountainous areas (the Mentissoideinae group), is also discussed.